2017
DOI: 10.1111/brv.12320
|View full text |Cite
|
Sign up to set email alerts
|

PPARs in the central nervous system: roles in neurodegeneration and neuroinflammation

Abstract: Over 25 years have passed since peroxisome proliferators-activated receptors (PPARs), were first described. Like other members of the nuclear receptors superfamily, PPARs have been defined as critical sensors and master regulators of cellular metabolism. Recognized as ligand-activated transcription factors, they are involved in lipid, glucose and amino acid metabolism, taking part in different cellular processes, including cellular differentiation and apoptosis, inflammatory modulation and attenuation of acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 346 publications
2
57
0
Order By: Relevance
“…There exist reports of FOXO3a, PGC-1α, and PPARγ elevation in animals fed a KD [42,126,127]. This is consistent with the work of several other authors who have reported that the upregulation of these transcription factors is driven by the upregulation of NAD + , AMPK, and SIRTs via a number of different routes [1,128].…”
Section: Consequences Of Ketogenesis and Ketolysis In The Cnssupporting
confidence: 90%
See 1 more Smart Citation
“…There exist reports of FOXO3a, PGC-1α, and PPARγ elevation in animals fed a KD [42,126,127]. This is consistent with the work of several other authors who have reported that the upregulation of these transcription factors is driven by the upregulation of NAD + , AMPK, and SIRTs via a number of different routes [1,128].…”
Section: Consequences Of Ketogenesis and Ketolysis In The Cnssupporting
confidence: 90%
“…The first stems from the fact that PPARα and PPARγ are the main transcription factorregulating ketogenesis and ketolysis and both PPAR isoforms are activated by increased levels of FFAs in the periphery and brain, a few days after the advent of ketosis [75,133,134]. The second is that several authors have reported that the upregulation of PPAR isoforms in the brain results in a reduction in neuroinflammation in vivo [125,126,135,136]. The third is that PPAR upregulation has the capacity to rescue mitochondrial dysfunction in the CNS environment typical of neurodegenerative [137] and neuroprogressive disorders [137,138].…”
Section: Consequences Of Ketogenesis and Ketolysis In The Cnsmentioning
confidence: 99%
“…PPARs and RXR receptors activation upregulates the expression of several synaptic related genes coding proteins engaged in excitatory neurotransmission [12,36]. Probably through these mechanism agonists of PPAR-α may have a promising effect in a mouse model of aging-dependent cognitive impairments [37,38]. Moreover, it was previously reported that RXR activation increases dendritic complexity and branching of neurons and differentiation [39,40] but it seems now that PPAR-α plays a key role in these processes.…”
Section: Ppar-α and Its Role In Neurotransmission In The Brainmentioning
confidence: 99%
“…PPAR-α activates also nuclear gene encoded pyruvate dehydrogenase kinase 4 (PDK4) which is also activated by PPAR-β/δ but inhibited by PPAR-γ [70]. In addition to the PPAR-α other PPARs receptors can be also involved in activation of gene coding acyl-CoA hydrolase enzyme and ω-hydroxylase cytochrome p450 4A subfamily (CYP4A) [38,71]. It was found that PPAR-α, PPAR-γ and its coactivator PGC-1α are very potent factors in mitochondria biogenesis through activation of mitochondrial transcription factor and several nuclear transcription factors: (TFAMtranscription factor A mitochondria, NRF1, NRF2, YY1, SP-1) ( Fig.…”
Section: The Role Of Ppars In Regulation Of Mitochondrial Functionmentioning
confidence: 99%
“…The interaction of PPAR-and NF-B has been implicated in certain central neural diseases [32]. PPAR-can inhibit the activity of NF-B by binding to the subunits P65 and P50 of NF-B and competing for common transcription coactivators such as SRC-1 and p300/CBP (CREB-binding protein) or upregulate inhibitor kappa B (I B) protein, which prevents NF-B nuclear translocation which is a prerequisite for NF-B activation.…”
Section: Discussionmentioning
confidence: 99%